La caricatura en Honduras: como manifestación artística y su importancia en la crítica socio/política: 1960-1980 - DÍAZ, Fredy José Macías (Universidade Federal do Pará, 2018)
The starting point of this work is to study the development of the caricature as an artistic expression in the local newspapers of the time, making an analysis of the discourse implicit in these cartoons. In a discussion about the importance that this had in the country between the 1960s and 1980s, an attempt will be made to interpret the socio-political context in which the cartoons were created, directly studying what happened in this period of history of the nation, highlighting the role played by the caricature as an element of criticism.